IN VITRO ACTIVITY AND COMPARATIVE STUDIES OF SOME ORGANOTIN(IV) BENZOATE DERIVATIVES AGAINST LEUKEMIA CANCER CELL, L-1210 - Sutopo Hadi; Mita Rilyanti; Suharso Suharso (Indonesian Journal of Chemistry, 2012)
A series of dibutyl-, diphenyl- and triphenyltin(IV) benzoate derivatives has been prepared. The products were obtained by reacting the dibutyltin(IV) dichloride, diphenyltin(IV) dichloride and triphenyltin(IV) chloride respectively via the dibutyltin(IV) oxide, diphenyltin(IV) dihydroxide and triphenyltin(IV) hydroxide with benzoate acid and its derivative. The targeted compounds have been tested with anticancer activity against leukemia cancer cell, L-1210. The compounds synthesized were well characterized by 1H and 13C NMR, IR and UV-Vis spectroscopies as well as based on the microanalytical data. The results showed that triphenyltin(IV) benzoate and its derivative prepared exhibit higher anticancer activity than those of dibutyltin(IV) and diphenyltin(IV) analogous.